PENINGKATAN KETERAMPILAN MELAGUKAN TEMBANG MACAPAT DENGAN MEDIA KASET AUDIO DAN GAMELAN - Suwarna . (Jurnal Cakrawala Pendidikan, 2004)
This article is based on a research on the possibility ofimproving the skill ofstudents in the Javanese Art class in performing the tradi tional Javanese singing activity called macapat by using audiocas settes and garnelan (traditional Javanese) musical instruments. The research used the Kemmis and McTaggart model ofaction research. The researcher teaches the class ofJavanese Traditional Singing at the Javanese Language Course Program, Faculty ofLan guages and Arts, State University ofYogyakarta. Thirteen students attending the Javanese Art class ofthe Course Program participated in the research. The researcher collaborated with Kusnadi, M.Pd., who teaches the Javanese Traditional Singing and Music class at the DanceArt Education Course Program ofthe Faculty, and was also a research team member. The research instruments were texts of Javanese songs, observation sheets, questionnaires, tests, audiocas settes, and garnelanmusical instruments. The validity ofinstruments was continued by means ofsemantic validation, the technique ofcheck and recheck, discussions with colleagues and the collaborator, and experts' judgment. The research was conducted in four cycles.The results of the research indicate that audiocassettes and garnelan musical instruments can improve the students' skill in per fonning the macapat singing activity. In improving that skill by using audiocassettes (I) students can conduct independent learning and (2) beginners can master the sense ofJavanese musical tone by imitation and playback, sharpened by listening to audiocassettes ofJavanese songs. By the end ofcycle three their mastery of that sense had begun to show some state ofbeing established. To establish it more finnly, it was necessary to conduct cycle four by utilizing the garnelan musical instruments, which clearly show some tone stability, in learn ing how to sing Javanese songs. With the use ofthe garnelan musical instruments (I) students learned to master their sensitivity ofthe tones (called slendro and pelog) by feeling them, (2) the tones they learned to sense were presented in an integrated way by means ofthe garnelan rhythm, (3) Javanese songs with a metrical scale were more easily mastered by students than those with a rhythmical one, (4) errors often occurred at the tone jumps called kempyung and gembyang, and (5) nearing the end ofthe research their mastery ofthe sense of tone more was better and more well-established. Students began to be able to learn Javanese songs by themselves .. Keywords: Javanese song, audiomedia, garnelan, sense ofngeng